Management of Endometrial Hyperplasia. Issue 7 (September 2015) - Kim, Mi Kyoung; Seong, Seok Ju; Kim, Jae-Weon; Bae, Duk-Soo; Jeon, Seob; Kwon, Sang-Hoon; Lee, Taek Sang
<x xml:space="preserve">Abstract</x> Objectives This study aimed to investigate the current management of endometrial hyperplasia (EH) in Korea. Materials and Methods This was an electronic survey, which included 40 questions, that was distributed to the members of the Korean Gynecologic Oncology Group in 2014. Results In total, 50 (69%) of 72 members responded to the survey. The oral progestogens were the most popular choices for managing EH without atypia (simple hyperplasia(SH), 64%; complex hyperplasia (CH), 52%). In the case of CH with atypia, most of the gynecologist respondents would perform hysterectomy (95.9%). For fertility preservation, the oral progestogens were the most popular choices (SH, 75.5%; CH, 56.3%), followed by the levonorgestrel-releasing intrauterine system (LNG-IUS). More than 70% of the respondents reported use of dilatation and curettage as a follow-up method. Conclusions Our survey results show that most of Korean gynecologic oncologists still prefer oral progestogens for conservative management of EH, notwithstanding the many successful reports on the LNG-IUS. As a follow-up evaluation method, dilatation and curettage is mostly used. To identify the optimum therapy, a randomized controlled trial comparing the LNG-IUS with continuous oral progestogens is required. Furthermore, a large-scale prospective study to confirm the most reliable technique for follow-up evaluation is necessary.